Eksplorasi Pengaruh UGC Media Sosial Terhadap Perencanaan Wisata - Regina Candrika; Sri Marhanah; Rosita Rosita (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
With the rapid development of social media as a major source of information for tourists in planning their trips, User Generated Content (UGC), such as reviews, photos, and travel experiences shared by other users, is considered more authentic and trustworthy than official promotions. This study aims to analyze the factors of User Generated Content (UGC) posted on social media that influence tourists’ travel planning, in order to understand tourists’ perceptions of the benefits of social media and the factors affecting the use of information in travel planning. This study employs a quantitative approach using a survey method involving tourists who utilize social media to access UGC related to tourism in their travel planning process. A total of 157 respondents who undertook trips during the period of October–November 2025 participated in this study. Data were analyzed using descriptive statistics and Exploratory Factor Analysis (EFA) to identify the underlying dimensions of UGC usage in travel planning, based on eigenvalues, factor loadings, and Varimax rotation. The results reveal that two main factors were identified, namely ease of use and trust in social media, as well as risk reduction and perceived benefits of social media, which together explain 60.879% of the total variance. These findings indicate that UGC plays a significant role in supporting tourists’ travel planning process.